Clima organizacional : percepção dos TAE's do Departamento de Gestão de Pessoas de uma IFES - Zardo, Cinthia Soares (2018)
The theme organizational climate has been object of great interest in recent years, both in academia and in business. It was observed that in the academic environment the interest is due to the fact that through the analysis of the several dimensions and factors that make up what is denominated organizational climate, the study of human behavior in organizations is deepened. In this sense, scholars from various areas were engaged in research on human behavior in organizations, interaction between individuals, factors that stimulated or discouraged the performance of activities, and the influence of the human factor on productivity and organizational performance. The purpose of this work was to show the aspects related to the organizational climate in the perception of public servants of the Department of People Management (DGP) of the Federal University of Espírito Santo (UFES)? The concern refers to the appreciation of people as one of the most important elements of the organizational structure, which is why the following question emerged: What is the level of satisfaction of crowded servers in the UFES Pro-Rector's Office of People Management? This research is justified because it treats the subject of high relevance for contemporary law, the dignity of the human person in the work environment. The methodology used was the descriptive research to better understand the researched topic. The steps to gather information were carried out in two moments, the first time the bibliographic survey and, in the second, the application of a questionnaire of closed and open questions to public sector employees, a total of 31 respondents. The final conclusions showed that most of the employees pointed out as negative aspect, towards the improvement of the physical structure of the sector. In turn, what aspects related to the manager's support, recognition and cohesion among colleagues are among the indicators of satisfaction among respondents. The research line of the present work fall as Management of People in the Public Sector. As a technical product, in the case of the professional master's degree, in addition to suggestions presented for other researches, the appendix presents the Diagnostic Report with the Action Plan, to be submitted to UFES, proposing changes in relation to the perceived problem, so that the be able to analyze it, adjust it if necessary, and implement it.